The Investigation of Sex Differences in the Effect of Body Mass Index - Xiang Xiao; Weihua Wang; Rina Sa; Lin Qiu; Feng Liu (International Journal of Hypertension)
Although many researches regarding risk factors for hypertension have been reported, little information is known about the effect of BMI on the prevalence of hypertension considering sex differences. The aim of this study was to examine the sex difference in the prevalence of hypertension with the predicting indicator BMI. A total number of 6330 subjects in Shaanxi were examined using multivariable logistic regression to study the relationship between genders in different levels of BMI and prevalence of hypertension. Overall, females had a higher prevalence of hypertension than males, being 28.36% and 21.55%, respectively. The mean of blood pressure and the prevalence of hypertension increased as BMI getting larger. The result of multivariable logistic regression showed that obese and overweight males had higher risk of getting hypertension than their female counterparts. Further prevention of hypertension should be focused on obese and overweight males more than females and examining the mechanism of how sex differences influence the prevalence of hypertension.